2016
DOI: 10.1186/s40550-015-0024-0
|View full text |Cite
|
Sign up to set email alerts
|

Variations in trace metal and aflatoxin content during processing of High Quality Cassava Flour (HQCF)

Abstract: Background: High Quality Cassava Flour (HQCF) has gained popularity in most parts of West Africa because of its versatility in many industries. However, due to the processing techniques used HQCF may contain trace metals and aflatoxins. Imperatively, the safety of HQCF was assessed when the levels of trace metal and aflatoxin contaminants was determined at the various unit operation during HQCF production.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 10 publications
3
7
1
Order By: Relevance
“…Limit of detection (LOD) and LOQ for aflatoxin was obtained using the formula; LOD = standard concentration at which no peak was observed (3*baseline noise/peak height) and LOQ = 2*LOD. The findings from the present work conforms to a similar work on aflatoxins content in High Quality Cassava Flour (HQCF) done by Ofori et al (2016) where aflatoxin B 1, B 2, G 1, and G 2 was not detected in all HQCF samples analyzed but contradict previous studies on aflatoxin determination in Maize, Sorghum, Millet and Water yam flour in some West African countries such as Ghana, Gambia and Nigeria. For example Kpodo (2001) conducted aflatoxin determination in maize from Ghana which revealed that eighty-four (84) out of one hundred and twenty-eight (128) maize kernel sampled from markets and maize processing sites were contaminated with aflatoxin at level up to 200 ng/g whiles a similar studies on aflatoxin determination in cereal-based food products intended for infants and young children done by Blankson and Mill-Robertson (2016) also showed aflatoxin contamination at levels of 0.18 ± 0.01 to 36.10 ± 0.32 μgkg −1 .…”
Section: Aflatoxin Analysessupporting
confidence: 88%
See 2 more Smart Citations
“…Limit of detection (LOD) and LOQ for aflatoxin was obtained using the formula; LOD = standard concentration at which no peak was observed (3*baseline noise/peak height) and LOQ = 2*LOD. The findings from the present work conforms to a similar work on aflatoxins content in High Quality Cassava Flour (HQCF) done by Ofori et al (2016) where aflatoxin B 1, B 2, G 1, and G 2 was not detected in all HQCF samples analyzed but contradict previous studies on aflatoxin determination in Maize, Sorghum, Millet and Water yam flour in some West African countries such as Ghana, Gambia and Nigeria. For example Kpodo (2001) conducted aflatoxin determination in maize from Ghana which revealed that eighty-four (84) out of one hundred and twenty-eight (128) maize kernel sampled from markets and maize processing sites were contaminated with aflatoxin at level up to 200 ng/g whiles a similar studies on aflatoxin determination in cereal-based food products intended for infants and young children done by Blankson and Mill-Robertson (2016) also showed aflatoxin contamination at levels of 0.18 ± 0.01 to 36.10 ± 0.32 μgkg −1 .…”
Section: Aflatoxin Analysessupporting
confidence: 88%
“…The highest concentrations of As, Hg and Pb determined in the seven flour samples were < 0.01, < 0.01, and 0.05 ± 0.01 mg/Kg respectively which were all below the WHO set limit of As, Hg and Pb in foods. The maximum concentration of Hg determined in the root and tuber and cereal flour samples was < 0.01 mg/Kg which is similar to that determined in cassava flour samples by Ofori et al (2016). Arsenic (As) and Pb was not detected in processed cassava flour samples analyzed in Ghana by Ofori et al (2016) but was detected in all the root and tuber and cereal flour sample analyzed presently even though their concentrations were within acceptable levels by WHO (WHO 1982).…”
Section: Trace Metal Analysessupporting
confidence: 71%
See 1 more Smart Citation
“…Emurotu et al 18 determined nine elements (K, Ca, Mg, Fe, Cu, Mn, Pb, and Cd) in cassava flour sold in Nigeria. On the other hand, Ofori et al 30 evaluated the levels of Cu, Fe, As, Hg, Pb and Zn in high quality cassava flour marketed in Ghana.…”
Section: Introductionmentioning
confidence: 99%
“…This result is an indication that home processing method can reduce the levels of Pb during boiling, frying and roasting. Ofori et al [ 34 ] did not detect Pb content in high quality cassava flour, a product from cassava obtained through a combination of several processing steps including drying. Oluyemi et al [ 35 ], on the other hand, reported Pb content ranging from 57.00 ± 0.02–87.50 ± 0.01 mg/kg for unprocessed cassava from farm lands close to areas where mining companies had previously dumped waste.…”
Section: Resultsmentioning
confidence: 99%